Effect of Effective Cough on Sputum Expulsion in Patients with ARI (Acute Respiratory Infection) - Indra Ruswadi; Roy Andri Yani; Tia Karlina; Fika Amalia (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
ISPA or ARI (Acute Respiratory Infection) is an acute respiratory illness that lasts about 14 days and usually affects the throat, nose and lungs. A frequent problem in patients with acute respiratory infections is the inability to clear secretions from the airways which can lead to ineffective airway clearance. One of the non-pharmacological management of ARI can be done with effective cough training. The purpose of this study was to determine the effect of effective cough on sputum discharge in patients with ARI at Sumber Kasih General Hospital, Cirebon City in 2022. This research design uses pre experiment with one group pre test-post test design. The research subjects were 90 ARI patients at Sumber Kasih General Hospital, Cirebon City with the sampling technique used was accidental sampling. The research instrument was a sputum discharge observation sheet. The results of the study obtained data from the pretest results showed that sputum discharge in patients with ARI before effective cough training was carried out in the outgoing category, namely 54 people (60%). While the results of the posttest showed that sputum discharge in patients with ARI after effective coughing exercises with the outgoing category was 81 people (90%). Based on the results of the Wilcoxon test, the significance value (sig.2-tailed) <0.05 (p=0.000), then based on the decision-making criteria, Ha is accepted, meaning that effective cough training can increase sputum discharge in patients with ARI at Sumber Kasih General Hospital, Cirebon City. It is hoped that nurses can provide education about effective cough training to increase sputum discharge in patients with ARI, so that patients with ARI are able to practice it at home